A Distributed Biogas Production Model and Its Use in the Livestock Sector. Case Study: Castile and León - Carlos Reparaz; Laura Sánchez-Martín; Ignacio de Godos; Pedro Mora; Bernardo Llamas (Applied Sciences, 2021)
The population increase and the food demand increase the fight against climate change. Porcine production in Europe continues to increase, and Spain is the leading country in pig production. Manure management has a significant environmental impact that requires anaerobic digestion technologies for its mitigation. This technology helps produce biogas, a fuel that will reduce CO2 emissions. This study defines a distributed biogas generation model, determining the expected incomes from the development of this technology in small manure generation facilities (digestible organic waste). The development of this technology will contribute to reduce the demand for fossil energy and increase revenues by 22.7% regarding the expected revenues from the use of biogas for electricity generation.